Pop-Up Book Media Based on Local Wisdom Within The Dimension of Global Diversity and Critical Thinking - Salsabila, Apriliana; Wulandari, Murfiah Dewi (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to investigate the effect of using local wisdom-based Pop-Up Book media on two key dimensions in fourth-grade elementary school students: global diversity and critical thinking. Methodology: The study employs a quantitative approach. The population consists of 220 fourth-grade students selected randomly from three elementary schools in Surakarta and its surrounding areas. The independent variable (X) is the Pop-Up Book media based on local wisdom, while the dependent variables (Y1 and Y2) are global diversity and critical thinking, respectively. Data were collected using questionnaires and analyzed through a Multivariate Analysis of Covariance (MANCOVA) to assess the simultaneous effects on both dependent variables. Data normality was confirmed with p-values of 0.098 for global diversity and 0.055 for critical thinking, both exceeding the 0.05 threshold. Results: The Wilks’ Lambda multivariate test yielded a value of 0.936, with F = 7.380 and a significance level of 0.001 (p < 0.05), indicating that the use of local wisdom-based Pop-Up Book media has a significant positive influence on students’ global diversity awareness and critical thinking skills. Applications/Originality/Value: The findings highlight the potential of culturally grounded instructional media to foster both global perspectives and higher-order thinking skills. By integrating local values into interactive learning tools, educators can create meaningful and engaging classroom experiences that promote cognitive and cultural competence among elementary students.